2019
DOI: 10.1002/mus.26767
|View full text |Cite
|
Sign up to set email alerts
|

Myotonic dystrophy type 1 alters muscle twitch properties, spinal reflexes, and perturbation‐induced trans‐cortical reflexes

Abstract: Background: Neurophysiologic biomarkers are needed for clinical trials of therapies for myotonic dystrophy (DM1). We characterized muscle properties, spinal reflexes (H-reflexes), and trans-cortical long-latency reflexes (LLRs) in a cohort with mild/ moderate DM1. Methods: Twenty-four people with DM1 and 25 matched controls underwent assessment of tibial nerve H-reflexes and soleus muscle twitch properties. Quadriceps LLRs were elicited by delivering an unexpected perturbation during a single-limb squat (SLS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…LLR in Myotonic Dystrophy Type 1 (DM1) (n = 1 Study): In a study of 24 patients with DM1, abnormalities in the muscle twitch properties such as reduced H-reflex depression with less robust LLR response was observed. 84…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LLR in Myotonic Dystrophy Type 1 (DM1) (n = 1 Study): In a study of 24 patients with DM1, abnormalities in the muscle twitch properties such as reduced H-reflex depression with less robust LLR response was observed. 84…”
Section: Resultsmentioning
confidence: 99%
“…83 LLR in Myotonic Dystrophy Type 1 (DM1) (n = 1 Study): In a study of 24 patients with DM1, abnormalities in the muscle twitch properties such as reduced H-reflex depression with less robust LLR response was observed. 84 LLR in Stroke (n = 3 Studies) and Neurorehabilitation (n = 1 Study): Results of LLR assessment among long term stroke-survivors were contradictory. 85,86,87 A more recent study by Bank C et al showed that stroke survivors with intact LLR, have a better clinical recovery with respect to walking speed and power of ankle flexors compared to healthy controls.…”
Section: Llr In Other Movement Disordersmentioning
confidence: 99%
“…Utilizing novel physiology measures of lower leg muscle function (soleus), our group recently showed that DM1 patients exhibited co-occurring alteration of spinal and trans-cortical reflex properties, providing strong support for the role of CNS abnormalities in muscle dysfunction in DM1 19 . Other neuroimaging studies have supported the notion that muscle impairment is linked to regional decreases in fractional anisotropy 12 , 13 .…”
Section: Discussionmentioning
confidence: 96%